Red and yellow, black and brown : decentering whiteness in mixed race studies - Rondilla, Joanne L.; Guevarra, Rudy P., Jr; Spickard, Paul R., 1950- (Rutgers University Press, 2017)
"Red and Yellow, Black and Brown gathers together life stories and analysis by twelve contributors who express and seek to understand the often very different dynamics that exist for mixed race people who are not part white. The chapters focus on the social, psychological, and political situations of mixed race people who have links to two or more peoples of color-- Chinese and Mexican, Asian and Black, Native American and African American, South Asian and Filipino, Black and Latino/a and so on. Red and Yellow, Black and Brown addresses questions surrounding the meanings and communication of racial identities in dual or multiple minority situations and the editors highlight the theoretical implications of this fresh approach to racial studies."--